Meningkatkan Kemampuan Motorik Halus Melalui Kegiatan Pengolahan Bahan Bekas Pada Anak Usia 5-6 Tahun di TK Aisyiyah Bustanul Athfal Banyuwangi - Nuryanah Nuryanah; Hariyanti Hariyanti; Helen F Sinambela; Widaningsih Widaningsih (Jurnal Pendidikan Tuntas, 2023)
Fine motor stimulation is an important aspect of early childhood development. If a child has not been able to develop his fine motor skills well, then the child will also experience difficulty in carrying out activities related to hand skills. The aim of this research is to improve fine motor skills through used material processing activities in children aged 5-6 years at the Aisyiyah Bustanul Athfal Kindergarten, Banyuwangi. Specifically, the used material used during the research was waste paper. This type of research is classroom action research. This research was carried out in two cycles and each cycle was held in two meetings. This research was carried out at the Aisyiyah Bustanul Athfal Banyuwangi Kindergarten with research subjects being Group B aged 5-6 years, totaling 16 people. Data collection in this research used observation and documentation techniques. From cycle 1 to cycle II, especially in the "Developing According to Expectations" category which increased from 26.67% to 53.33%. In addition, children who were in the "Undeveloped" category in cycle 1 had reached 0% in cycle 2, showing a positive increase in the fine motor development of group B children aged 5-6 years at the Aisyiyah Bustanul Athfal Banyuwangi Kindergarten. The achievements in cycle 2 were in accordance with the established indicators of success, so that the classroom action research was considered complete and successful in improving children's fine motor skills. Keywords: Fine Motor Skills, Used Materials, ECE